Pengaruh Expressive Writing Therapy terhadap Tingkat Kecemasan pada Mahasiswa Tahun Pertama Fakultas Kedokteran Universitas Sam Ratulangi - Sallo, Asdi; Opod, Hendri; Pali, Cicilia; Munayang, Herdy (JURNAL BIOMEDIK : JBM, 2020)
Abstract: Novice students can experience anxiety due to their difficulty in adjusting the new environment. There are several ways to overcome the anxiety, one of them by writing (expressive writing therapy). Expressive writing therapy is a way to write traumatic experiences about hidden emotions. This study was aimed to determine the effect of expressive writing therapy on anxiety levels of first-year students of the Medical Education Study Program at the Faculty of Medicine, Sam Ratulangi University. This was a quantitative study using the true experimental method and randomized pretest-posttest control group design. There were 40 students as respondents, divided into two groups (control and experimental groups). The results showed that in the control group there was no difference in knowledge between pretest and posttest (p=0.878) (Î±>0.05), meanwhile in the experimental group, there were significant differences between the pretest and posttest p=0.000 (Î±<0.05). In conclusion, expressive writing therapy could reduce the anxiety level of first year students of the Medical Education Study Program, Faculty of Medicine, Sam Ratulangi University.Keywords: expressive writing therapy, anxiety level, first year studentsÂ Abstrak: Mahasiswa baru dapat mengalami derajat kecemasan karena sulit untuk menye-suaikan diri dengan lingkungan baru. Terdapat beberapa cara untuk mengatasi kecemasan, salah satunya dengan menulis (expressive writing therapy). Expressive writing therapy meru-pakan cara untuk menuliskan pengalaman traumatik mengenai emosi yang tersembunyi. Penelitian ini bertujuan untuk mengetahui pengaruh expressive writing therapy terhadap tingkat kecemasan mahasiswa tahun pertama Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi. Jenis penelitian ialah kuantitatif dengan metode true experimental, dan randomized pretest-posttest control group design. Responden penelitian ialah 40 mahasiswa tahun pertama, dibagi atas 2 kelompok (kontrol dan eksperimen). Hasil penelitian memperlihatkan pada kelompok kontrol tidak terdapat perbedaan pengetahuan pretest dan posttest (p=0,878; Î±>0,05). Hasil pretest dan posttest kelompok eksperimen memperlihatkan perbedaan (p=0,000; Î±<0,05). Simpulan penelitian ini ialah expressive writing therapy berpengaruh terhadap penurunan tingkat kecemasan mahasiswa tahun pertama Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi.Kata kunci: expressive writing therapy, tingkat kecemasan, mahasiswa tahun pertama